Compensation Settlement for Breach of Contract in Land Lease Agreements from the Perspective of Islamic Economic Law - Rahmadita, Azizah; Musykaroh, Yufi Wiyos Rini; Kurniati, Herlina (UIN Fatmawati Sukarno Bengkulu, 2026)
Abstracts: This analysis purposes to identify the settlement of compensation arising from default in a land lease agreement as well as to examine it from the Islamic economic law perspective. The analysis motivated by land leasing practices that do not fully protect tenants’ rights, particularly when the landowner sells the leased object before the lease period ends. The research was conducted in Karang Tumaritis Village, Kotabumi Utara District, North Lampung, using a qualitative technique with a case study approach. Data collected from the interviews, observations, as well as documentation implicating parties directly engaged in the land lease agreement. The results show that the landowner committed default by failing to fully deliver the benefits of the leased object and by selling the land while the lease period was still ongoing without notifying the tenant. From the positive law view, this action violates the provisions of Articles 1243 and 1548 of the Indonesian Civil Code. Meanwhile, from the Islamic economic law perspective, such conduct contradicts the principles of the ijarah contract, which emphasize justice (‘adl) and trustworthiness. The tenant’s total financial loss is estimated at approximately IDR 11,000,000. Dispute resolution was carried out through deliberation (ṣulḥ), resulting in an agreement to provide partial compensation amounting to IDR 5,500,000, accompanied by the tenant’s act of relinquishment (ibrā’). This settlement is considered consistent with justice principle and public interest (maṣlaḥah) in law of Islamic economic. Keywords: Compensation; Default; Ijarah; Islamic Economic Law.Abstrak : Analisis ini bertujuan untuk mengidentifikasi penyelesaian kompensasi yang timbul akibat wanprestasi dalam perjanjian sewa tanah serta untuk mengkajinya dari perspektif hukum ekonomi Islam. Analisis ini dimotivasi oleh praktik sewa tanah yang tidak sepenuhnya melindungi hak penyewa, khususnya ketika pemilik tanah menjual objek sewa sebelum masa sewa berakhir. Penelitian ini dilakukan di Dusun Karang Tumaritis, Kecamatan Kotabumi Utara, Lampung Utara, menggunakan teknik kualitatif dengan pendekatan studi kasus. Data dikumpulkan dari proses wawancara, observasi serta dokumentasi langsung pada pihak-pihak yang terlibat dalam perjanjian sewa. Hasil penelitian menunjukkan bahwa pemilik tanah melakukan wanprestasi dengan gagal memberikan manfaat objek sewa secara penuh dan dengan menjual tanah tersebut sementara masa sewa masih berlangsung tanpa memberitahukan kepada penyewa. Dari perspektif hukum positif, tindakan ini melanggar ketentuan Pasal 1243 dan 1548 KUHP Indonesia. Sementara itu, dari perspektif hukum ekonomi Islam, tindakan tersebut bertentangan dengan prinsip-prinsip kontrak ijarah, yang menekankan keadilan ('adl) dan kepercayaan. Total kerugian finansial penyewa diperkirakan sekitar Rp 11.000.000. Penyelesaian sengketa dilakukan melalui musyawarah (ṣulḥ), menghasilkan kesepakatan untuk memberikan kompensasi sebagian sebesar Rp 5.500.000, disertai dengan penyerahan hak milik (ibrā’) oleh penyewa. Penyelesaian ini dianggap sesuai dengan asas keadilan keadilan dan kepentingan umum (maṣlaḥah) dalam hukum ekonomi Islam. Kata kunci: Ganti Rugi; Hukum Ekonomi Syariah; Ijarah; Wanprestasi.